PENGARUH KETERSEDIAAN KOLEKSI TERHADAP KUNJUNGAN PEMUSTAKA DI PERPUSTAKAAN UNIVERSITAS NEGERI PADANG - Aisyahtul Husna; Nurizzati Nurizzati (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
This study aims to describe how the availability of collections, library visits and the effect of collection availability on library visits at the Padang State University Library. This type of research is quantitative research with descriptive methods. The population in this study is the number of users who visit the Padang State University library on average in the early 6 months of 2021 totaling 2,163 people, and a sample of 100 people. This sampling was determined based on purposive sampling technique which is a sampling technique with certain considerations. The research data was obtained by distributing questionnaires through the Google Form application by distributing the questionnaire links to respondents. Data analysis was carried out descriptively using the formula for calculating relative frequencies and percentages. The results obtained in the availability of collections, library visits and the effect of collection availability on user visits to Padang State University are 2.70 which are on an interval scale of 2.51 – 3.25, so it can be seen that the effect of collection availability on visitor visits to the University Negeri Padang belongs to the high category.